Nasal Epidermal Inclusion Cyst in a horse: Case Report - Psyllaki, M; Diakakis, N (Journal of the Hellenic Veterinary Medical Society, 2022)
Nasal epidermal inclusion cysts, previously known as “atheroma” or “sebaceous cyst”, are cutaneous lesions that occur in the caudodorsal aspect of the nasal diverticulum, between the epithelium of the diverticulum and the skin of the nostril. They are mostly benign, asymptomatic, non-painful, and are primarily of cosmetic significance. Nasal epidermal inclusion cysts are rather rare in horses in contrast with other species or humans. According to our knowledge, nasal epidermal inclusion cysts have not previously been reported across the Mediterranean basin. A 12-year-old, Warmblood gelding was presented to the Equine unit, Aristotle University of Thessaloniki for evaluation of a facial swelling on the right side of the nose. The swelling was first observed 2 years before presentation and had progressively increased in size. On presentation, the horse was bright, alert, responsive and all parameters of the clinical examination were within normal limits. The presence of a large, fluctuating cyst, of approximately 6cm in diameter was noted on the caudodorsal aspect of the right nasal diverticulum. Based on the location and clinical characteristics, a diagnosis of nasal epidermal inclusion cyst was made, and surgical removal was elected. Following anesthesia, a linear skin incision up approximately 8cm long, directly over the epidermal inclusion cyst was made through the skin and subcutaneous tissues. The cyst was dissected from the surrounding tissues, drainage of the wound into the false nostril was done by making a 2-cm incision from the defect into the false nostril and the operating site was thoroughly lavaged. The horse was re-examined 2 months later and showed complete resolution of clinical signs with no complications. The surgical wound had closed completely leaving no obvious scar. The horse was still blemish - free two years after surgery.